Calibrating and testing the discrete element parameters for peanut seedling film - Peng, Qiangji; He, Xin; Li, Guoming; Yang, Rusha; Wang, Xiaoyu; Zhang, Chunyan; Zhang, Ningning; Kang, Jianming (International Journal of Agricultural and Biological Engineering, 2024)
This study constructed a numerical model using the discrete element software EDEM to address the current lack of calibrated contact parameters for peanut seedling membranes and the absence of precise simulation model parameters for mechanized separation. The Hysteretic Spring Contact Model (HSCM) was employed to calibrate the contact parameters of peanut seedling membranes. The angle of repose of peanut seedling membranes was determined through image processing combined with the least squares method. Through central composite design (CCD), a second-order response model linking the contact parameters to the angle of repose was established. Optimization was achieved by using the angle of repose obtained from physical tests as the objective. Secondary simulation tests were conducted with the calibrated parameters, revealing a relative error of 1.37% between the simulated and physical angles of repose. This confirmed the effectiveness of the parameters in calibrating peanut seedling membrane characteristics. The findings offer theoretical and empirical support for discrete element simulations of peanut seedling membrane separation and peanut straw pulverization processes. Keywords: discrete element method, peanut, post-crumbled seedling film, angle of repose, contact parameters, calibration DOI: 10.25165/j.ijabe.20241705.9087 Citation: Peng Q J, He X, Li G M, Yang R S, Wang X Y, Zhang C Y, et al. Calibrating and testing the discrete element parameters for peanut seedling film. Int J Agric & Biol Eng, 2024; 17(5): 65-72.